To study the frequency of dysplasia and carcinoma in cervical smears, their clinical presentation and their correlation with koilocytosis, presence of x-chromatin and their association with HSV - 2. - Bashyal, Reeta (2001)
ABSTRACT: A total of 1,106 cases were studied during a one year period from 1/11/2056 to 30/10/2057. Majority of the lesions were Fast smears constituting 91.0%, Cervical intraepithelial neoplasia [CIN] and squamous cell carcinoma [SCC] cervix constituted 8.0 and 1.0% respectively. The percentage of different grades of CIN being CIN I 85.0%, CIN I-II 5.0%, CIN II 4.0%, CIN II-III 2.0% and CIN III 4.0%. Thirty cases were taken as a study group. The commonest age group for CIN was 31-40 years 80.0% and for Carcinoma cervix above 50 years 63.0%. The most common risk factors were marriage before 20 years of age 80.00% and a low socioeconomic status 70.0%. The common presenting feature in CIN was pain lower abdomen 88.0% followed by whitish discharge per vagina and anorexia 60.0% each. Similarly in Carcinoma cervix pain lower abdomen 80.00% followed by weight loss 60.0% were the common presenting symptoms. Koilocytic change was seen in 41.0% of the cases of CIN I. The incidence of x-chromatin positivity gradually decreased is the lesion advanced, the p value between CIN I and CIN II (p=<0.02), CIN I and CIN III (p=0.00) and between CIN III and carcinoma cervix (p=<0.004) being significant. An association with HSV-2 was seen in 10.6% caes of CIN I, 33.3% cases of CIN III and 40.0% cases of Carvinoma cervix with a gradual rising antibody time of 1:2 in CIN I, 1:7 in CIN III and 1:7 to 1:9 in Carcinoma cervix respectively.